Creative community organizing : a guide for rabble-rousers, activists, and quiet lovers of justice - Kahn, Si (BK currents book., 2010)
"Privatization has been on the right-wing agenda for years. Health care, schools, Social Security, public lands, the military, prisons -- all are considered fair game. Through stories, analysis, impassioned argument -- even song lyrics -- Si Kahn and Elizabeth Minnich show that corporations are, by their very nature, unable to fulfill effectively what have traditionally been the responsibilities of government. They make a powerful case that the market is not the measure of all things, and that a vital public sector is an indispensable component of a healthy democracy."--Provided by publisher